PENGARUH KEBERADAAN BANDARA INTERNASIONAL KUALANAMU TERHADAP PERUBAHAN SOSIAL EKONOMI MASYARAKAT DI SEKITARNYA - Isnaini Harahap, Sri Ramadhani, Langga Tri Ayu, (Islamic Circle, 2021)
The purpose of this study was to determine the effect of the existence of Kualanamu on changes in livelihoods, income and welfare, education, housing and public health. The method used is quantitative research with primary data collection techniques in the form of questionnaires distributed to 95 respondents. Analysis of the data used in this study is the analysis of paired sample t-test using SPSS version 23.0. The results of the t-test sample test showed that all variables had significant differences in changes in livelihoods, income, education, housing, and health between before and before the Kualanamu airport. This is evidenced by the value of Sig (2 tailed) 0.000 the value is less than 0.05 (0.000 <0.05), then H0 is rejected and Ha is accepted. social economy. The perceived economic changes are people's income caused by changes in livelihoods so that they can absorb labor which automatically increases people's living standards. people lose the opportunity to have the opportunity to open a business. So it can be said that the existence of Kualanamu Airport has an impact on the socio-economics of the surrounding community.